TAM Model Analysis of QRIS Use Preferences with a Structural Equation Modelling Approach: An Empirical Study of GMIM Youth - Modaso, Paske V.; Barek, Titya A. P. (Celebes Scholar pg, 2025)
This study aims to analyze the influence of perceived usefulness (PU) and perceived ease of use (PEOU) on QRIS usage preferences among GMIM Youth using the Technology Acceptance Model (TAM) approach. The research method used is quantitative explanatory with primary data collection through questionnaires from 120 respondents selected by purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0 software. The results of the measurement model testing (outer model) showed that all indicators met the validity and reliability criteria. In the structural model testing (inner model), both hypotheses were proven significant: PEOU had a positive and significant effect on usage preferences (β = 0.483; p-value = 0.000), as did PU (β = 0.357; p-value = 0.000). The R² value of 0.602 indicates that the PU and PEOU variables are able to explain 60.2% of the variation in QRIS usage preferences. The conclusions of this study reinforce the TAM postulate that technology adoption, in this case QRIS, is largely determined by the perceived ease and usefulness of use. Consequently, service providers and relevant authorities are advised to continue improving the ease of use of the interface and promoting the benefits of QRIS, particularly within the context of religious communities.